# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = 2 x y-x^{3}+x
\] |
✓ |
✓ |
|
\[
{}y-x y^{2} \ln \left (x \right )+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3}+3 x^{2} y+y^{2}-y^{3}+\left (2 y^{3}+3 x y^{2}+x^{2}-x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y-x}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \ln \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -x +\sqrt {x^{2}+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -x -\sqrt {x^{2}+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{\prime } \sqrt {1-x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x y-x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (y \cos \left (y\right )-\sin \left (y\right )+x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x}-x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \arcsin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = \arctan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y-1
\] |
✓ |
✓ |
|
\[
{}x^{5} y^{\prime }+y^{5} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (-2 x^{2}+1\right ) \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (y\right ) = x^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+1+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y\right )-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sin \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}-4\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) \left (x^{2}+1\right ) y^{\prime } = 2 x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x -2 y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x^{2}+1
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{-y}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 \cos \left (3 x \right ) \cos \left (2 y\right )-2 \sin \left (3 x \right ) \sin \left (2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \left (1+x \right ) \left (1+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y+1
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = g -\frac {k v^{2}}{m}
\] |
✓ |
✓ |
|
\[
{}x^{2}-2 y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-3 x y-2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 3 \left (x^{2}+y^{2}\right ) \arctan \left (\frac {y}{x}\right )+x y
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 x \,{\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x -y-\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x +3 y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 2 x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3}+y^{3}-y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x -y+1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x -y-6}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x +y-6}
\] |
✓ |
✓ |
|
\[
{}2 x -2 y+\left (y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y-1}{x +4 y+2}
\] |
✓ |
✓ |
|
\[
{}2 x +3 y-1-4 \left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-x y^{2}}{2 x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2+3 x y^{2}}{4 x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y-x y^{2}}{x +x^{2} y}
\] |
✓ |
✓ |
|
\[
{}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}y-x^{3}+\left (x +y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}1+y+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1 = \frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 y^{4} x +\sin \left (y\right )+\left (4 x^{2} y^{3}+x \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime }+y}{1-x^{2} y^{2}}+x = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1+\sqrt {x^{2}-y}\right ) = \sqrt {x^{2}-y}\, y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \ln \left (y\right )+x y+\left (y \ln \left (x \right )+x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{2}}-\csc \left (y\right ) \csc \left (x \right )^{2}+\left (2 x y \,{\mathrm e}^{y^{2}}-\csc \left (y\right ) \cot \left (y\right ) \cot \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2} \sin \left (2 x \right )-2 y \cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x}{\left (x^{2}+y^{2}\right )^{{3}/{2}}}+\frac {y y^{\prime }}{\left (x^{2}+y^{2}\right )^{{3}/{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} \left (1+\ln \left (y\right )\right )+\left (\frac {x^{3}}{y}-2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {-x y^{\prime }+y}{\left (x +y\right )^{2}}+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\frac {4 y^{2}-2 x^{2}}{4 x y^{2}-x^{3}}+\frac {\left (8 y^{2}-x^{2}\right ) y^{\prime }}{4 y^{3}-x^{2} y} = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x^{2}-y^{2}\right ) y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y-1+\left (x^{2}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y+3 x^{3} y^{4} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+\left ({\mathrm e}^{x} \cot \left (y\right )+2 y \csc \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right ) \sin \left (y\right )+x \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (x -2 x^{2} y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +3 y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|